EFEKTIVITAS PELAYANAN PEMBAYARAN PENSIUN PEGAWAI NEGERI SIPIL DI PT. TASPEN CABANG MANADO - Embisa, Rahnia; Kiyai, Burhanuddin; Tampongangoy, Deysi (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstract: this study aims to facilitate any work that was conducted in Ministry effectiveness seehow retirement payment of civil servant in PT Taspen Manado Branch. Based on the results of thestudy Branch PT Taspen Manado need to increase retirement payment service so that there is no delayin payment of retirement services.Research methods in this study is a qualitative research method, and data collectiontechniques in the study ofobservation/observation directly to the location of research, conduct interviews, and documentation.The results showed there is still a delay in the payment of pensions of the Ministry civilservant in PT Taspen. branch of Manado. So there is no delay in payment of thepension service in influence by the performance, each of the fields that exist in theOffice Branch Taspen Manado.Keywords: Effectiveness Of Service, Payment Of The Pension